(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the quality of life and associated factors among hemodialysis patients at Duc Giang General Hospital. Subjects and methods: A cross-sectional descriptive study was conducted on 122 patients with end-stage renal disease undergoing maintenance hemodialysis at Duc Giang General Hospital between 2025 and 2026. Results: The mean overall quality of life score was 58.05 ± 11.20, with mean physical and mental health scores of 57.50 ± 16.12 and 58.60 ± 12.12, respectively. Older age, a greater number of comorbidities, and lower educational level were significantly associated with poorer quality of life (p < 0.05). These findings highlight the need for comprehensive and individualized patient care. Conclusion: The quality of life among patients undergoing maintenance hemodialysis was at a moderate level. Factors such as age, the number of comorbidities, and educational level were associated with quality of life.